Students’ Perceptions on Chemistry Education Programme: A Qualitative Inquiry in Faculty of Education - Acharya, Kamal Prasad (Interdisciplinary Research in Education, 2024)
This article examines the efficacy of the Chemistry Education program offered by the Department of Science and Environment Education, Central Department of Education, Tribhuvan University. It also explores students' perceptions and experiences regarding the program, focusing on its strengths and challenges. Using purposive sampling, ten students enrolled in the Science Education program were selected for data collection through face-to-face interviews and conversations. Verbatim and conversational analyses were employed to analyze the data. The findings indicate that the culture of teaching and learning has shifted from traditional, teacher-centered approaches to student-centered pedagogies, with a strong emphasis on research-based and project-oriented learning. Students appreciated the comprehensive coverage of theoretical concepts in the Chemistry Education program. However, they expressed concerns about the limited opportunities for practical laboratory work, which they felt hindered their ability to fully grasp and apply the concepts learned in class. Additionally, the study found that while the program integrates theoretical constructs with real-world applications through experiential learning modalities, doubts persist regarding its effectiveness in cultivating skills essential for long-term professional success. It is strongly recommended to elevate the Chemistry Education program by integrating more dynamic and interactive pedagogical approaches to more effectively nurture the skills critical for sustained professional success.